2011
DOI: 10.1105/tpc.110.081802
|View full text |Cite
|
Sign up to set email alerts
|

BENT UPPERMOST INTERNODE1Encodes the Class II Formin FH5 Crucial for Actin Organization and Rice Development  

Abstract: The actin cytoskeleton is an important regulator of cell expansion and morphogenesis in plants. However, the molecular mechanisms linking the actin cytoskeleton to these processes remain largely unknown. Here, we report the functional analysis of rice (Oryza sativa) FH5/BENT UPPERMOST INTERNODE1 (BUI1), which encodes a formin-type actin nucleation factor and affects cell expansion and plant morphogenesis in rice. The bui1 mutant displayed pleiotropic phenotypes, including bent uppermost internode, dwarfism, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
112
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(121 citation statements)
references
References 103 publications
(170 reference statements)
8
112
1
Order By: Relevance
“…Further, the osarf23/35S::RMD plants exhibited stronger longitudinal F-actin bundles with higher density compared with those of the WT (Fig. 3 C-G), consistent with a role for RMD in actin bundling organization (22,23). In response to IAA, osarf23 also displayed less sensitivity with respect to auxin-regulated root cell growth and RMD expression and the rearrangement of F-actin arrays (Fig.…”
Section: Heterodimers Ofsupporting
confidence: 63%
See 2 more Smart Citations
“…Further, the osarf23/35S::RMD plants exhibited stronger longitudinal F-actin bundles with higher density compared with those of the WT (Fig. 3 C-G), consistent with a role for RMD in actin bundling organization (22,23). In response to IAA, osarf23 also displayed less sensitivity with respect to auxin-regulated root cell growth and RMD expression and the rearrangement of F-actin arrays (Fig.…”
Section: Heterodimers Ofsupporting
confidence: 63%
“…RMD plays a pivotal role in regulating morphogenesis by modulating cytoskeleton organization in rice (22,23). To investigate the role of RMD during rice root growth, we used two null mutant alleles of RMD, rmd-1 and rmd-2 (22).…”
Section: Rmd-mediated F-actin Organization Controls Cell Growth Andmentioning
confidence: 99%
See 1 more Smart Citation
“…F-actin was stained using the previously described method (Olyslaegers and Verbelen, 1998;Yang et al, 2011;Zhang et al, 2011). Mature rice leaves were incubated in PEM buffer (100 mM PIPES, 10 mM EGTA, 0.3 M mannitol, and 5 mM MgSO 4 , pH 6.9) and 0.66 mM Alexa Fluor 488-phalloidin (Life Technologies).…”
Section: Fluorescence Microscopy Of Actin Filamentsmentioning
confidence: 99%
“…Our previous work demonstrated that a type II formin protein, RICE MORPHOLOGY DETERMINANT (RMD; also called BENT UPPERMOST INTERNODE1) from rice (Oryza sativa), functionally regulates cytoskeleton organization by nucleating, capping, and bundling actin in vitro and also plays a crucial role in regulating F-actin dynamics and arrays in rice cells (Yang et al, 2011;Zhang et al, 2011;Li et al, 2014). rmd mutants exhibit altered microfilament and microtubule arrays, causing defective plant morphology .…”
mentioning
confidence: 99%